2012
DOI: 10.1002/ajmg.b.32085
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis argues for a female‐specific role of MAOA‐uVNTR in panic disorder in four European populations

Abstract: Panic disorder (PD) is a common mental disorder, ranking highest among the anxiety disorders in terms of disease burden. The pathogenesis of PD is multifactorial with significant heritability, however only a few convincing risk genes have been reported thus far. One of the most promising candidates is the gene encoding monoamine oxidase A (MAOA), due to its key role in monoaminergic neurotransmission, established validity of animal models, and the efficacy of MAO inhibitors in the treatment of PD. A promoter r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 51 publications
4
36
1
Order By: Relevance
“…Genomic DNA of all individuals included in the case-control study was extracted from venous blood by a routine desalting method. The discovery sample was described previously 32 and consisted of 239 PD patients recruited in Germany (female=143, male=96; mean age 37.6+11.1). The diagnosis of PD and presence of comorbid agoraphobia (PD/AG; 68.6%; n=75) was ascertained by experienced psychiatrists on the basis of medical records and structured clinical interviews (Composite International Diagnostic Interview, CIDI) according to the criteria of DSM-III-R or DSM-IV, respectively [33][34][35] .…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA of all individuals included in the case-control study was extracted from venous blood by a routine desalting method. The discovery sample was described previously 32 and consisted of 239 PD patients recruited in Germany (female=143, male=96; mean age 37.6+11.1). The diagnosis of PD and presence of comorbid agoraphobia (PD/AG; 68.6%; n=75) was ascertained by experienced psychiatrists on the basis of medical records and structured clinical interviews (Composite International Diagnostic Interview, CIDI) according to the criteria of DSM-III-R or DSM-IV, respectively [33][34][35] .…”
Section: Samplesmentioning
confidence: 99%
“…8) was obtained from the national research initive "Panic-Net" founded by the Federal Ministry of Education and Research 36 ; details on the sample as well as the study workflow were previously published 32,37 . The diagnosis of PD/AG (co-morbid AG was an inclusion criterion, so all patients suffered thereof) was established by a structured clinical interview (CIDI) according to DSM-IV criteria 35 .…”
Section: Samplesmentioning
confidence: 99%
“…Also Lung et al [28] found that the 5-repeat allele had a low frequency (0.54% in males) with major depressive disorder. In addition, a low frequency of the 5-repeats allele was also observed in females with panic disorder [29].…”
Section: Discussionmentioning
confidence: 88%
“…Gender-specific associations with depression have been shown in glutamate decarboxylase 1 gene single-nucleotide polymorphisms (SNPs) [1], α 2 -/β 2 -adrenoceptor gene polymorphisms [2], cAMP response element binding protein 1 [3] and monoamine oxidase A upstream variable number tandem repeat (MAOA-uVNTR) [4]. Associations between panic disorder and the glutamate decarboxylase 1 gene SNPs [5], MAOA-uVNTR [6] and neuropeptide S receptor gene [7] have also been detected.…”
Section: Introductionmentioning
confidence: 99%